2021
DOI: 10.1177/00469580211028174
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Sustainability in Healthcare Sector through Fintech: Analyzing the Moderating Role of Financial and ICT Development

Abstract: Healthcare organizations are setting new targets of sustainable practices to improve their financial performance without depleting social and natural capital. Maintaining a sustainable, resilient, and durable healthcare system facilitate economies to achieve sustainable competitiveness. Thus, it is important to address and fill the knowledge gap by identifying factors that improve a firm’s sustainability. Drawing on technological knowledge spillover theory, this study investigates the effect of FinTech develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…This finding is also supported by Deng et al ( 14 ), who noted that an inconclusive digital financial system supports sustainable development and plays a role in coherence with the social, economic, environmental, and governance. Meiling et al ( 31 ) argued that Fintech encourages countries to achieve sustainable development without compromising social, economic, and environmental performance. Fintech is a modern pillar of the economy in the globe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also supported by Deng et al ( 14 ), who noted that an inconclusive digital financial system supports sustainable development and plays a role in coherence with the social, economic, environmental, and governance. Meiling et al ( 31 ) argued that Fintech encourages countries to achieve sustainable development without compromising social, economic, and environmental performance. Fintech is a modern pillar of the economy in the globe.…”
Section: Resultsmentioning
confidence: 99%
“…FinTech is also facilitated society by reducing income inequality, providing better healthcare services to deprived income groups, and improving the financial sector performance of the healthcare industry. Our study follows the latest empirical studies ( 28 , 31 ). To detect the impacts of FinTech on health outcomes; we have used the following panel model forms:…”
Section: Model and Methodsmentioning
confidence: 99%
“…Consistent with the technological knowledge spillover theory, ref. [9] found that FinTech development improves the sustainable performance of 59 healthcare firms in 11 Asia-Pacific countries. Meanwhile, ref.…”
Section: Fintech Adoption and Sustainability From An Sis Perspectivementioning
confidence: 99%
“…These digital technologies are designed to improve production efficiencies, the key competitive advantage to survive modern, globalized markets. The combination of efficiency-driven property and digital structure makes I-4.0 technologies promising change agents for sustainability [1][2][3][4][5][6][7] and sustainable development [8][9][10]. They eliminate processes and resources that have caused irreversible environmental problems, resource depletion, and ecological imbalances [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation